LEXICAL LACUNARITY AND ITS REFLECTION IN TRANSLATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Today, scientists of the world are increasingly interested in the study of lacunae. The term lacuna has gained a strong place in Uzbek linguistics and translation studies. As a result, a special field of "lacunology" was created in linguistics. This article is devoted to the learning process of lacunae in the language.